Conversion, circumcision, and ritual murder in medieval Europe - Tartakoff, Paola (Middle Ages series., 2020)
Inspired by one fascinating and unusual historical case, Conversion, Circumcision, and Ritual Murder in Medieval Europe explores the ways religious conversion fueled Jewish-Christian tensions. In the process, it elucidates how the interplay of fact and fantasy shaped Christian views of Jews as agents of Christian apostasy to Judaism.